CHO-K1 cells expressed IGF-1 Gene: a promising target towards optimal media at effective cost - Packeer Mohamed, Vasila; Hasyim, Yumi Zuhanis Has-Yun; Amid, Azura; Mel, Maizirwan; Kamarulzaman, Abdul Wahab; Abdul Wahab, Muhammad Adil; Mohamed Saberi, Salfarina Ezrina (2011)
Insulin-like growth factor-1 (IGF-1) has been shown to promote cell proliferation and inhibit apoptosis of cells. These are two characteristics in mammalian cell culture which may lead to high density cell culture producing optimal desired yield of bioproducts. IGF-1 has also been recognized in treatment of growth failure and cancer. This study is set to investigate IGF-1 gene expression in Chinese Hamster Ovary (CHO-K1) cells and its relationship with cellular behavior at different time points of cell growth. CHO-K1 cells were first cultured in T-flask with three independent experiments. An 8-hourly sampling for responses (glucose and lactate), (total protein and biomass) were taken. For IGF-1 gene detection, PCR-based method for selected time points was performed. Results from the study showed that CHO-K1 cells expressed IGF-1 gene. This suggests that IGF-1 plays a role in cell roliferation. The study confirms the IGF-1 expression in CHO-K1 cells. It also provides the baseline data for CHO-K1 cell growth which is important for future studies using CHO-K1 cells especially it is a promising target towards optimal media at effective cost.